EXPLORING POTENTIALS AND CHALLENGES OF MICROLEARNING IN ESP AND ESP MATERIALS DESIGN: A SYSTEMATIC REVIEW - Caroline, Stephani Fahra; Sumarni, Sri; Darmahusni, Darmahusni (Universitas Muhammadiyah Metro, 2023)
The intrigue surrounding microlearning's potential in English for Specific Purposes (ESP) has motivated this research, aiming to delve into its applications and challenges in ESP and its materials design. This study explores the potential and impediments of employing microlearning in ESP, focusing on its material design and instructional methodology. Through a systematic literature review, five pertinent articles from 2016-2022 were selected and analyzed using platforms like Publish or Perish and Google Scholar. The findings reveal a limited yet impactful application of microlearning in ESP, highlighting its capacity to enhance learning through the facilitation of digital materials, bite-sized and self-paced learning, and student empowerment, among other benefits. In ESP materials design, microlearning stimulates learning and underscores the importance of integrating multimedia into the learning process. However, challenges such as the need for appropriate technology, poor learning initiative, creation of a new learning culture, students’ time constraints, teachers’ unfamiliarity with technology, and the need for adaptive material design based on microlearning principles, material development, and ESP materials, emerge as significant hurdles. This research implies a valuable pathway for future studies and practical applications, offering insights into navigating through these challenges and optimizing the application of microlearning in ESP and its material design, thereby contributing to the field's pedagogical development.